Pseudogenization of NK3 homeobox 2 (Nkx3.2) in monotremes provides insight into unique gastric anatomy and physiology - Jackson Dann; Zhipeng Qu; Linda Shearwin-Whyatt; Rachel van der Ploeg; Frank Grützner (Open Biology, 2024)
The enzymatic breakdown and regulation of food passage through the vertebrate antral stomach and pyloric sphincter (antropyloric region) is a trait conserved over 450 million years. Development of the structures involved is underpinned by a highly conserved signalling pathway involving the hedgehog, bone morphogenetic protein and Wingless/Int-1 (Wnt) protein families. Monotremes are one of the few vertebrate lineages where acid-based digestion has been lost, and this is consistent with the lack of genes for hydrochloric acid secretion and gastric enzymes in the genomes of the platypus (Ornithorhynchus anatinus) and short-beaked echidna (Tachyglossus aculeatus) . Furthermore, these species feature unique gastric phenotypes, both with truncated and aglandular antral stomachs and the platypus with no pylorus. Here, we explore the genetic underpinning of monotreme gastric phenotypes, investigating genes important in antropyloric development using the newest monotreme genomes (mOrnAna1.pri.v4 and mTacAcu1) together with RNA-seq data. We found that the pathway constituents are generally conserved, but surprisingly, NK3 homeobox 2 (Nkx3.2) was pseudogenized in both platypus and echidna. We speculate that the unique sequence evolution of Grem1 and Bmp4 sequences in the echidna lineage may correlate with their pyloric-like restriction and that the convergent loss of gastric acid and stomach size genotypes and phenotypes in teleost and monotreme lineages may be a result of eco-evolutionary dynamics. These findings reflect the effects of gene loss on phenotypic evolution and further elucidate the genetic control of monotreme stomach anatomy and physiology.